Reintroduced White Storks (Ciconia ciconia) Have Similar Diets to Their Wild Conspecifics - Şeniz Mustafa; Connor T. Panter; Laura Vaughan‐Hirsch; Rachel L. White; Anja Rott (Ecology and Evolution, 2025)
ABSTRACT Understanding a species' diet is crucial for assessing its ecology and can indicate the success of reintroduction efforts. We explored dietary composition and compared pellet morphology and supplementary prey proportions between two white stork (Ciconia ciconia) groups to assess reintroduction effectiveness. White stork groups consisted of released individuals that were free flying (i.e., “wild group”) and those kept within a confined enclosure (“captive group”). A total of 23 white stork pellets were collected during the 2023 breeding season. Wild group pellets were significantly heavier (x̄ = 12.7 ± 9.2 g [SD]) than captive group pellets (x̄ = 5.2 ± 2.1 g). As expected, all captive group pellets contained supplementary prey, accounting for 88.4% ± 26.1% of pellet biomass, whereas 73.3% of wild group pellets contained supplementary prey, comprising 52.9% ± 36.3% of pellet biomass. The wild group predominantly foraged on beetles (Coleoptera) and earthworms (Clitellata). Our results represent the first quantitative dietary assessment of reintroduced white storks in southern England. Similarities between our data and that of wild white stork diets from elsewhere in their range suggest successful post‐release acclimatisation at Knepp Estate.